Return of Rin Tin Tin - Nosseck, Max; Rin-Tin-Tin (Dog); Woods, Donald, 1906-1998; Romay Pictures Inc.; Cinetel Films ([United States?] : Romay Pictures Inc., 1947)
A youngster from Europe, unable to adapt to his new surroundings, finds affections in a faithful dog. --
Released by Eagle-Lion Films, Inc.
Donald Woods, Bobby Blake, Gaylor Pendleton, Claudia Drake.
Cinematographer, Carl Berger; editors, Michael Luciano, Elmo J. Veron; music, Erdody.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015)
Keywords: Rin-Tin-Tin -- (Dog) -- Drama; German shepherd dog -- Drama; Animal films; Feature films; Internet videos; Streaming video